Bentuk, Fungsi, dan Distribusi Reduplikasi Kata Benda Bahasa Melayu dan Bahasa Jepang - Ong, Shyi Nian; Hamzah, Zaitul Azma Zainon (Journal of Japanese Language Education and Linguistics, 2020)
Reduplication is a process of multiplying words in which many new words can be generated, and the process has a lexical function that can maintain the class-maintaining or class-changing (word-changing) of a word, as asserted by Asmah (2001: 17-35) that â€œReduplication has a lexical function; that is to say it derives new words from the root-formsâ€™â€™. This study aims to make reduplication of contrasting qualitative descriptive nouns existing in languages other than English and Japanese. The comparisons were carried out between the two languages aiming to examine similarities and differences in function or reduplication of nouns in both Malay and Japanese. The data were taken from the libraries, such as Takayama (2012), Osato (2013), Kobayakawa (2004), Tamura (1991) and Matsumoto (2009) for the Japanese, and Asmah (1975) and Abdullah (1974) for the Malay, and analyzed by comparing elements of similarities and differences existing in both languages. Among the interesting findings is the name word â€œhitoâ€ (person) in Japanese to â€œhito-bitoâ€ (people), showing the change of consonant / h / to / b / in its first syllable, which can be categorized as reduplication with the change of sound. Likewise with Malay, there is a change in the consonant sounds in â€œlauk paukâ€, in which / l / becomes /p/ and in â€œsayur-mayurâ€ / s / becomes / m / when pluralized.